Design of Digital Squeeze Frame Console for Public Service Advertisement - Astin, Novita; Ceraka, Nandhita Ayundra Wulintang (Jurnal Teknologi Informasi dan Pendidikan, 2022)
Digital advertisement is one of the promotional media used by producers to embed brands in the memory of their consumers. However, in the current era, digital advertising is not only used to promote a brand but in delivering public service advertisements, digital advertising is often used. This is because, with the development of the digital era, digital advertising is accepted by the public more quickly. There are various types of digital advertising, including Squeeze Frame. The process of running Squeeze Frame using the Vmix software. Vmix software is a virtual mixer that runs using a keyboard and mouse. In a broadcasting process, especially in outdoor areas, long distances in the process of controlling audio-video broadcasting become one of the obstacles. So there are limitations in running the Vmix software which can only be run using the keyboard and mouse. In this research, an alternative tool is created that can be used when running Vmix software in console form. The form of console hardware is easy to carry so that the broadcasting process using Vmix software can be carried out more easily. By using Arduino Uno CH340 as a microcontroller, the console not only adjusts the audio-video input but also adjusts the squeeze frame display. The result of this research is that the hardware console runs well, for the squeeze frame merging button for public service advertisements. Respondents are interested in this console with a percentage of 95.8%